Karakteristik Brownies Panggang dengan Substitusi Tepung Bengkuang (Pachyrizus erosus L.) dan Pemanis Daun Stevia (Stevia Rebaudiana Bertoni M.) - Arif Prashadi Santosa; Agus Mulyadi Purnawanto (Universitas Muhammadiyah Purwokerto, 2021)
This study aimed to find out the effect of jicama flour substitution, and stevia leaf substitution as the sweetener, and the interaction on proximate and sensory characteristic of baked brownies. The research was conducted using a completely randomized design (CRD) consisting of two factors. The first factor was the substitution ofjicama flour (B) with 4 levels of the jicama flour: 30%(B1), 40% (B2), 50%(B3), and 60%(B4). The second factor was the concentration of stevia leaves as the sweetener (S) with 3 levels: 1.75 grams (S1), 2.75 grams(S2), and 3.75 grams (S3). Proximate analysis parameters included moisture content, ash content, fat content, total sugar content, crude fibre content, and swelling power test. Sensory test parameters included colour, texture, aroma, taste and preference. The results indicated that the substitution treatment of jicama flour (B) had a significant effect on proximate analysis especially on the variable of total sugar content, crude fibre content, and swelling power. While the sensory properties had no significant effect on all variables. The treatment of adding stevia leaves (S) had a significant effect on the proximate analysis on ash content, total sugar content, and crude fibre content variables; and on sensory analysis, it affected the texture variable. The treatment interaction (SxB) had a significant effect on proximate analysis on several variables (ash content, total sugar content, fibre content, and swelling power), while sensory analysis had no significant effect on all variables. The best treatment was based on proximate and sensory analysis on the treatment of adding 1.75-gram stevia leaves and 60% jicama flour substitution (S1B4) with 22.67% water content, 1.44% ash content, 25.67% total sugar content, 28.85%fiber crude content, swelling power of 64.72%, colour of 4.00 (slightly dark brown), texture of 2.00 (thick), the aroma of 4.13 (slightly delicious), taste of 3.13 (slightly sweet), and preference of 3.33 (slightly like).